Neoadjuvant radiotherapy in ER+, HER2+, and triple-negative -specific breast cancer based humanized tumor mice enhances anti-PD-L1 treatment efficacy - Bruss, Christina; Albert, Veruschka; Seitz, Stephan; Blaimer, Stephanie; Kellner, Kerstin; Pohl, Fabian; Ortmann, Olaf; Brockhoff, Gero; Wege, Anja K. (Frontiers in Immunology, 2024)
Pre-operative radiation therapy is not currently integrated into the treatment protocols for breast cancer. However, transforming immunological "cold" breast cancers by neoadjuvant irradiation into their "hot" variants is supposed to elicit an endogenous tumor immune defense and, thus, enhance immunotherapy efficiency. We investigated cellular and immunological effects of sub-lethal, neoadjuvant irradiation of ER pos., HER2 pos., and triple-negative breast cancer subtypes in-vitro and in-vivo in humanized tumor mice (HTM). This mouse model is characterized by a human-like immune system and therefore facilitate detailed analysis of the mechanisms and efficiency of neoadjuvant, irradiation-induced "in-situ vaccination", especially in the context of concurrently applied checkpoint therapy. Similar to clinical appearances, we observed a gradually increased immunogenicity from the luminal over the HER2-pos. to the triple negative subtype in HTM indicated by an increasing immune cell infiltration into the tumor tissue. Anti-PD-L1 therapy divided the HER2-pos. and triple negative HTM groups into responder and non-responder, while the luminal HTMs were basically irresponsive. Irradiation alone was effective in the HER2-pos. and luminal subtype-specific HTM and was supportive for overcoming irresponsiveness to single anti-PD-L1 treatment. The treatment success correlated with a significantly increased T cell proportion and PD-1 expression in the spleen. In all subtype-specific HTM combination therapy proved most effective in diminishing tumor growth, enhancing the immune response, and converted non-responder into responder during anti-PD-L1 therapy. In HTM, neoadjuvant irradiation reinforced anti-PD-L1 checkpoint treatment of breast cancer in a subtype -specific manner. According to the "bench to bedside" principle, this study offers a vital foundation for clinical translating the use of neoadjuvant irradiation in the context of checkpoint therapy.